-3x/4 + 9/4 = (1/2)^x + 1
-3x/4 - 2^-x = -5/4
(Using log rules)
㏑|-3x/4| - ㏑|2^-x| = ㏑|-5/4|
㏑|3x/4| - x㏑|2| = ㏑|5/4|
e^㏑|3x/4| - e^㏑|2|x = e^㏑|5/4|
|3x/4| - 2x = 5/4
|3x| - 8x = 5
|3x-8x| = 5
|-5x| = 5
|5x| = 5
x=1, -1
Let
x-----------> <span>the side length of a pyramid square base
h-----------> t</span>he height of the sculpture <span>in the shape of a pyramid
we know that
h=(x-3)
Volume=162 cm</span>³
Volume=x² *(x-3)/3
then
x² *(x-3)/3=162----------> x³-3x²=486----------> x³-3x²-486=0
x³-3x²-486=0-------- <span>this equation can be used to find the length of the sculpture’s base
using a graph tool-----------> </span>to find the solution
x=9 cm -------------> see the attached figure
h=(x-3)-----> h=9-3--------> h=6 cm
the answer is
<span>
the length of the sculpture’s base is 9 cm</span>
the height of the sculpture is 6 cm
Answer:
19b-4
Step-by-step explanation:
7b+3(4b-2)+6÷3
Bracket comes first so we distribute 3 over the terms in the bracket
= 7b + 12b -6 +6 ÷ 3
First we solve division
= 7b + 12b -6 +6 ÷ 3
= 7b + 12b -6 +2
= (7b+12b)+(-6+2)
= 19b -4
This can't be simplified further as it can't be solved anymore
Answer:
if u divide it then slop it u will get your answer
Answer:
4/2, 2/7, 1/2, 5/6 is your answer